HUMOR DALAM AKTIVITAS TABLIGH - Japarudin Japarudin (Institut Agama Islam Negeri Bengkulu, 2017)
Tabligh is one way of doing Islamic da’wah, in addition to preachers and listeners, tabligh message is an important part of tabligh. The phenomenon of humor brought about by preachers among recent tabligh messages, and as if humor in tabligh have become a tabligh listener’s need, has led to many studies of the use of humor in Islamic da’wah. In this paper it describes how ideally humor should be presented in tabligh, a Qur’anic textual message, good humor and fair submission in tabligh, theories of humor that can be knowledgeable when it comes to humor, and the use of humor in tabligh.